Analisis Risiko Non Karsinogenik Pajanan PM10 di Kawasan Komersial, Kota Jambi - Rizki Andre Handika; Solikhati Indah Purwaningrum; Resti Ayu Lestari (Jurnal Serambi Engineering, 2019)
PM 10 Pollutant is an air particulate that cannot be detected by a nose hair. It contains carcinogenic and non-carcinogenic chemical components. This study, therefore, aims to quantify the concentration of PM 10 and identify the risks of the non-carcinogenic type’s exposure to the public’s health in the commercial area of Pasar Jambi sub-district. Measurement of PM  concentration was performed on Sunday (weekend) and Monday (weekday) using high volume air sampler (HVAS). Furthermore, questionnaire and interviewing were implemented on 95 people amounting to 12% of the total population. The result shows that PM 10  concentrations were observed to have exceeded ambient air quality standards of 196.9 µg/m3 on weekend and 2.094 µg/m3 weekday. Further- more, the average concentration of Al and Mn in PM 10  were 1.69384 µg/m3 and 0.04191 µg/m3 respectively. Although the public health activity was already at the risk of PM10 non-carcinogenic exposure in the commercial district (i.e RQ 1), there has notbeen any environmental health risks for the non-carcinogenic metals (Al and Mn) to the society. Therefore, risk management is carried out to protect the population from PM risks. Risk management comprises calculating the safe concentration, duration, frequency, and time of exposure on these weekend and weekday